2017
DOI: 10.1002/pc.24387
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory and mechanical properties of TPU/ABS blends: The role of pristine versus organo‐modified carbon nanotubes

Abstract: Some shape‐memory materials were prepared based on TPU/ABS blends containing pristine and organo‐modified multiwalled carbon nanotubes (MWCNTs). The shape memory and mechanical properties of the samples were investigated. Scanning electron microscopy (SEM) analysis performed on the morphological features of the developed samples showed the presence of pristine MWCNTs and decreased diameter of ABS droplets which were uniformly distributed within TPU matrix. Unexpectedly, the ABS droplets in nanocomposites with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
(88 reference statements)
1
9
0
Order By: Relevance
“…It can be seen that the Rf remains basically constant at the same TSW, but increases with the temperature because of more movement of the chain segments in the amorphous region, such as 90% at 85 °C, 95% at 100 °C, and 100% at 115 °C, which is consistent with the research of Wu et al [50]. In particular, The shape recovery process is the process of releasing the energy stored during the deformation at T SW [51]. Compared with the maximum value (approximately 77%) of R r of UHMWPE at 100 • C, it can be seen from Figure 10b that the R r of each group sample ranges from 48% of 13PEW5CS at 115 • C to 79% of 13PEW at 100 • C, which indicates that the addition of PEW and CS does not significantly improve the R r of UHMWPE.…”
Section: Shape Memory Behaviorssupporting
confidence: 87%
“…It can be seen that the Rf remains basically constant at the same TSW, but increases with the temperature because of more movement of the chain segments in the amorphous region, such as 90% at 85 °C, 95% at 100 °C, and 100% at 115 °C, which is consistent with the research of Wu et al [50]. In particular, The shape recovery process is the process of releasing the energy stored during the deformation at T SW [51]. Compared with the maximum value (approximately 77%) of R r of UHMWPE at 100 • C, it can be seen from Figure 10b that the R r of each group sample ranges from 48% of 13PEW5CS at 115 • C to 79% of 13PEW at 100 • C, which indicates that the addition of PEW and CS does not significantly improve the R r of UHMWPE.…”
Section: Shape Memory Behaviorssupporting
confidence: 87%
“…In this stage, the shape recovery and chain relaxation are observed . In case of TPU/ABS blend, with incorporation of ABS the crystallinity of neat TPU increased , which shows the nucleating role of ABS in the blend . This increment in the degree of crystallization can enhance the shape fixity.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, it was also reported that addition of ABS to TPU may deteriorate its tensile strength, which placed stress on the use of carbon‐based nanofillers like MWCNTs . As mentioned in our previous works , TPU and ABS are immiscible because of differences in their chemical nature and polarity; therefore, their blends show a clear two‐phase morphology. The relatively large spherical droplets of ABS phase were dispersed in TPU matrix and there is not strong interfacial adhesion between these components, and as a result, the tensile strength of the TPU/ABS blend decreases with increasing ABS content .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations